Aplicação de metodologia de preços hedônicos ao mercado brasileiro de serviços de comunicação e mídia - Leite, Gleidson Augusto Ribeiro Ferro (2009)
The Brazilian market of multimedia services presents one of the highest growth rates among all countries in the world. A large part of this growth can be attributed to technological developments and recent changes in the competitive environment, which promoted the convergence of services that were sold separately before - voice, data and TV. This process increased the joint appeal of these services, also contributing to the reduction of their price, mainly through gains of scale, spurring their growth. This high growth attracted more competitors to market, what, intensified by regulatory changes, increases the importance of correct pricing of services packages. Therefore, a proper understanding of the attributes most valued by consumers in the purchase decision-making process for these types of services is of crucial importance to improve the allocation of resources and maximize the return without loss of market share. This work applies the Hedonic Price Methodology as a tool to identify relevant attributes of multimedia services packages marketed in the city of São Paulo and their implicit prices. Around 370 diverse packages containing one to three different types of services are analyzed based on prices as of March 2009. As a result, were identified relevant premiums associated with Telecine related channels, children's and sports channels, movies and series channels, as well as variables representing download and upload speed.